Acute bacterial conjunctivitis – antibiotic susceptibility and resistance to commercially available topical antibiotics in Nepal - Shrestha, Sachet Prabhat; Khadka, Jagat; Pokhrel, Amod K; Sathian, Brijesh (Nepalese Journal of Ophthalmology, 2016)
Introduction: There is a shifting trend in susceptibility and resistance of the bacteria towards available antibiotics in the last decade. Therefore, periodic studies to monitor the emerging trends in antibiotic susceptibility and resistance are crucial in guiding antibiotic selection. Objectives: The aim of this study was to determine the most common pathogens causing bacterial conjunctivitis, and to find the in vitro susceptibility and resistance of these pathogens to commercially available topical antibiotic eye drops in Nepal. Subjects and methods: Conjunctival smears and antibiotic sensitivity tests were performed for 308 patients presenting to the Eye Care Center, Padma Nursing Home, Pokhara, Nepal from 11th December 1012 to 4th October 2013 with clinical signs and symptoms of acute infective conjunctivitisin in a hospital based cross-sectional study. Antibiotic sensitivity tests were performed for thirteen commercially available topical antibiotics- Chloroamphenicol, Moxifloxacin, Ofloxacin, Ciprofloxacin, Gentamycin, Tobramycin, Neomycin, Bacitracin, Polymyxin-B, Methicillin, Cephazoline, Amikacin and Vancomycin. Results: Acute infective conjunctivitis and viral conjunctivitis was more common in adults and in males. Bacterial conjunctivitis was present in about one third (32.47% to 36.04%) of the patients with acute infective conjunctivitis, and it was more common in children. Bacteria were highly sensitive (93-98%) to most commercially available antibiotics but significant resistance was found against three antibiotics-Bacitracin (9.0%), Neomycin (16.0%) and Polymyxin-B (24.0%). MRSA infection was found in 7.0% of the bacterial isolates. Rest of antibiotics, showed variable resistance (14.3% to 100.0%). All cases of Ophthalmia neonatorum were bacterial. Conclusion: The best commercially available antibiotic for bacterial conjunctivitis was Moxifloxacin. Nepal J Ophthalmol 2016; 8(15): 23-35